From the jewisch sabbat to the islamic Friday: A religious interpretation of the 62nd sura of the Koran: al-dschumu´a (“the synagogue”?) - Schmitz, Bertram (Vox Scripturae - Revista Teológica Internacional, 2025)
From a historical view, the Koran was created in the context of Judaism and Christianity, especially in their shape of the 7th century in the Near East. Many Suras are directly related to biblical texts and rituals of these religions. This also refers to the relation to the Friday as the “Day of assembly”. In the 62nd Sura it can be seen that this day is related to the Jewish Sabbath. As much as the translation and its understanding is done literally, as much the relation becomes clearly. In that sense the (later given) title of this Sura can be also translated as “Synagogue” in its literally sense. Later the Sura was understood as the foundation of the Islamic “Friday”. This kind of transformation is shown in the following article.
Keywords: Judaism and Quran; Sabbath and Friday; Poetical polemics